2020
DOI: 10.2459/jcm.0000000000000914
|View full text |Cite
|
Sign up to set email alerts
|

Clinical predictors of pocket hematoma after cardiac device implantation and replacement

Abstract: Aims Pocket hematoma is a common complication of cardiac implantable electronic device (CIED) procedures. the aim of the study was to research the clinical factors associated with pocket hematoma formation after CIED implantation or replacement and to identify the best perioperative antithrombotic management. Methods We retrospectively analyzed 500 consecutive patients who underwent to CIED implantation or replacement at our center from November 2014. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Several studies have assessed the occurrence of pocket hematoma, from 0.9% to 28.7%. (16,(22)(23)(24)(25)(26). In BRUISE CONTROL trial, the clinically significant device-pocket hematoma occurred in 12 of 343 patients (3.5%) in the continued-warfarin group, as compared with 54 of 338 (16.0%) in the heparin bridging group (27).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have assessed the occurrence of pocket hematoma, from 0.9% to 28.7%. (16,(22)(23)(24)(25)(26). In BRUISE CONTROL trial, the clinically significant device-pocket hematoma occurred in 12 of 343 patients (3.5%) in the continued-warfarin group, as compared with 54 of 338 (16.0%) in the heparin bridging group (27).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that device complexity and the number of leads were significantly associated with increased infection risk [17]. In one study, the infection risk was higher in implantable device replacement procedures than in first implants [18]. Also, patients with comorbidities such as congestive heart failure, renal failure, and thrombocytopenia have an increased risk of pocket hematoma formation [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…published. 3,4,6,7,16,19,[24][25][26] However, the BRUISE CONTROL study 1 correspondingly found aspirin to be an independent predictor of CSH (RR 2.04; 1.19-3.48), and a subsequent combined analysis of BRUISE CONTROL 1 and 2 concluded that concominant antiplatelet therapy doubles the risk of CSH. 27 When taking into consideration the widespread use of aspirin, especially among older adults, 28 the patient specific benefit/risk of holding aspirin when undergoing elective or semi-urgent CIED surgery, should be carefully considered.…”
Section: Risk Of Cshmentioning
confidence: 99%